The Effect of Surfactant Characteristics on IFT to Improve Oil Recovery in Tempino Light Oil Field Indonesia - Boni Swadesi; Taufan Marhaendrajana; Leksono Mucharam; H.P. Septoratno Siregar (Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
Water injection has been employed in the Tempino oil field since 1996. The current oil recovery factor is 35% of OOIP. Even though the pressure is still high, the oil production rate has declined rapidly and the water cut is approaching 89%. In order to mobilize the oil from the reservoir more effectively, surfactant flooding is one of the solutions that can reduce residual oil saturation. Interaction between crude oil and compatible surfactant generates microemulsion, as an indication of low interfacial tension. Hence the oil is expected to move out of the pore throat easily. In this research, thirty types of surfactants were evaluated. The hydrophilic lipophilic balance (HLB) was calculated and the interfacial tension (IFT) with the reservoir fluid was measured. HLB criteria were established as an indicator of low IFT, which was then tested for Berea core flooding. The results indicate that an HLB between approximately 2.7 and 3.1 (on Davies' Scale) or greater than 11.5 (on Griffin's Scale) gives low IFT ( 10-3 dynes/cm). This characteristic is possesed by surfactant ethoxy carboxylate with a linear hydrophobic structure. This surfactant produces a high incremental oil recovery according to Berea core flood tests. The AN2NS and AN3 surfactants recovered 90% and 86% of OOIP respectively.